An analysis of how dividend policy affects Corporate Value Investment Opportunities and Institutional Ownership as Moderating Variables - Desy Ihtiyarini; Hendar, Hendar (CV. Ulil Albab Corp, 2025)
This research seeks to investigate the influence of dividend policy on firm value, with investment opportunities and institutional ownership serving as moderating variables, focusing on energy sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The study employs purposive sampling as its sampling method. The population data of the study were 87, and a sample of 10 companies was obtained. The analytical method employed in this study is multiple linear regression analysis. The results demonstrate that dividend policy does not exert a significant impact on firm value, and investment opportunities fail to moderate the relationship between dividend policy and firm value and institutional ownership is able to moderate the effect of dividend policy on firm value. Adjusted R² = 0.427; Institutional ownership significantly moderates the relationship (β = 1.000, p = 0.000), while dividend policy and investment opportunity have no significant effect. Dividend policy and investment opportunity Exhibit no statistically significant impact on firm value (p > 0.05).